Licença compulsória para medicamentos como política pública: o caso do anti-retroviral efavirenz - Hoirisch, Cláudia (2010)
The scope of this study is to evaluate the implementation process of the Compulsory License in the case of the antiretroviral efavirenz. This research is descriptive in nature and the medium of investigation was the case study. It was conducted during the months of October through December 2009 with semi-structured interviews containing open-ended questions with a group of Public Health policy makers and managers residing in the states of Rio de Janeiro, Sao Paulo and the Federal District who participated in the compulsory license process. These individuals were allowed to express themselves without any constraints in such a way that they could produce discourses. The Collective Subject Discourse (CSD) technique was then used for analysis of the discourses. The results revealed that Brazil has the technological capability to develop and produce antiretrovirals within a reasonably short period of time. The results further showed that the Compulsory License helped to curb spending on antiretrovirals and that the measure can be used to ensure access by the public to high-cost and strategic antiretroviral drugs for the Brazilian public health service (Unified Health System – SUS) in an environment with limited funds, whenever an impasse is reached in negotiations for price reductions with transnational pharmaceutical laboratories.